Analisis indikator kriteria diagnosa keperawatan ketidakefektifan perfusi jaringan perifer dengan ankle brachial presur index lansia - Supriatna, Lalu Dedy; Nadrati, Bahjatun; Oktaviana, Elisa (Holistik Jurnal Kesehatan, 2025)
Background: Ankle Brachial Index (ABI) is a ratio of ankle and brachial systolic pressure that can be used to assess the severity of peripheral arterial occlusion, which is a general description of arterial blockage. If peripheral perfusion increases, it means that the adequacy of blood flow in distal blood vessels to support tissue function increases, with the outcome criteria to prove that peripheral perfusion increases, namely increased peripheral pulse strength, decreased pale skin color, improved capillary refill, improved acral, and improved skin turgor. Purpose: To analyzing the nursing diagnosis criteria indicators for ineffective peripheral tissue perfusion with ankle brachial pressure index in the elderly. Method: Cross sectional in studying the ankle brachial pressure index (ABPI) as a criterion indicator for establishing a nursing diagnosis of ineffective peripheral tissue perfusion in the elderly with a sample size of 45 respondents. The results of the bivariate test of the relationship between the nursing diagnosis criteria indicators of ineffective peripheral tissue perfusion in the elderly at the Mandalika NTB Elderly Social Service Center consisting of six independent variables, namely the results of the CRT examination, skin color, acral, Edema, Peripheral Pulse, and the results of the Edinburgh claudication questionnaire (ECQ), on the right ankle brachial pressure index. Results: Only the Peripheral Pulse has a significant relationship with the results of P Value 0.015 <0.05 and on the left ankle brachial pressure index is not much different from the results of the right ankle brachial pressure index, only the Peripheral Pulse has a significant relationship with the results of P Value 0.006 <0.05, and the other five independent variables do not have a significant relationship with the ankle brachial pressure index. Conclusion: Most respondents who have a normal peripheral pulse value in one minute will also have a normal ankle brachial index value.   Keywords: Ankle Brachial Presure Index; Elderly; Peripheral tissue perfusion.   Pendahuluan: Ankle brachial index (ABI) adalah ratio tekanan sistolik ankle dan brachial dapat digunakan untuk menilai severitas oklusi arteri perifer yang merupakan gambaran penyumbatan arteri secara umum. Jika perfusi perifer meningkat berarti keadekuatan aliran darah pembuluh darah distal untuk menunjang fungsi jaringan meningkat dengan kriteria hasil untuk membuktikan bahwa perfusi perifer meningkat adalah kekuatan nadi perifer meningkat, warna kulit pucat menurun, pengisian kapiler membaik, akral membaik, turgor kulit membaik. Tujuan: Untuk menganalisis indikator kriteria diagnosa keperawatan ketidakefektifan perfusi jaringan perifer dengan ankle brachial presur index lansia. Metode: Cross sectional dalam mempelajari ankle brachial pressure index (ABPI) sebagai indikator kriteria untuk menegakkan diagnosa keperawatan ketidakefektifan perfusi jaringan perifer pada lansia dengan jumlah sampel yaitu 45 responden. Hasil uji bivariat hubungan antara indikator kriteria diagnosa keperawatan ketidakefektifan perfusi jaringan perifer pada lansia di Pusat Pelayanan Sosial Lanjut Usia (PPSLU) Mandalika NTB yang terdiri dari enam variabel bebas yaitu hasil pemerikasaan CRT, warna kulit, akral, Edema, Nadi Perifer, dan hasil kuesioner klaudikasio Edinburgh (ECQ), pada ankle brachial presur index kanan. Hasil: Hanya nadi perifer yang memiliki hubungan yang signifikan yaitu dengan hasil p-value 0.015 < 0.05 dan pada ankle brachial presur index kiri tidak jauh berbeda dengan hasil ankle brachial presur index kanan, hanya Nadi perifer yang memiliki hubungan yang signifikan yaitu dengan hasil p-value 0.006 < 0.05, dan kelima varriabel bebas lainnya tidak memiliki hubungan signifikan dengan ankle barachial presur index. Simpulan: Sebagian besar responden yang memiliki nilai denyut nadi perifer normal dalam satu menit akan memiliki nilai ankle brachial index yang normal juga.   Kata Kunci: Ankle Brachial Index; Ketidakefektifan Perfusi Jaringan Perifer; Lansia.